2008
DOI: 10.1017/s0959270908000026
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation in mortality of the Bearded Vulture Gypaetus barbatus in Europe

Abstract: SummaryWe analyse the causes of mortality for the Bearded Vulture in Europe. Shooting (31%), intentional poisoning (26%), collision (18%) and unintentional poisoning (12%) were the most important causes of mortality. No differences were found between sexes or age classes (nonadults and adults) for any of the causes of death. When the four main categories of mortality were grouped in periods of 3 years from 1986 (coinciding with the species' reintroduction to the Alps) to 2006, mortality showed significant temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
109
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 21 publications
4
109
0
2
Order By: Relevance
“…For example, causes of mortality of Bearded Vulture carcasses collected in the study area over a similar time period indicated that death was almost entirely a result of anthropogenic factors, with more than half attributed to indirect and accidental poisoning and persecution, and almost a quarter to power line collisions (S. C. Krüger personal observation). Similarly, non-natural mortalities attributed to illegal poisoning were the main mortality factors in other Bearded Vulture populations (Margalida et al 2008) and other large raptor populations (Whitfield et al 2004, Smart et al 2010, and collisions with power lines are known to threaten other vulture species in Africa (Smallie andVirani 2010, Boshoff et al 2011). Impacts related to human disturbance were also found to limit the distribution patterns of Bearded Vulture and other large raptor breeding ranges, densities, and foraging areas (Brown 1988, Herremans and Herremans-Tonnoeyr 2000, Donázar et al 2002, Bautista et al 2004, Gavashelishivili and McGrady 2006, Margalida et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, causes of mortality of Bearded Vulture carcasses collected in the study area over a similar time period indicated that death was almost entirely a result of anthropogenic factors, with more than half attributed to indirect and accidental poisoning and persecution, and almost a quarter to power line collisions (S. C. Krüger personal observation). Similarly, non-natural mortalities attributed to illegal poisoning were the main mortality factors in other Bearded Vulture populations (Margalida et al 2008) and other large raptor populations (Whitfield et al 2004, Smart et al 2010, and collisions with power lines are known to threaten other vulture species in Africa (Smallie andVirani 2010, Boshoff et al 2011). Impacts related to human disturbance were also found to limit the distribution patterns of Bearded Vulture and other large raptor breeding ranges, densities, and foraging areas (Brown 1988, Herremans and Herremans-Tonnoeyr 2000, Donázar et al 2002, Bautista et al 2004, Gavashelishivili and McGrady 2006, Margalida et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Vultures in particular have experienced large population declines worldwide as a result of loss of suitable breeding and foraging habitat and poisoning , Oaks et al 2004, Ogada et al 2012. The Bearded Vulture (Gypaetus barbatus; Figure 1) is also showing declines throughout much of its range (Mingozzi and Estève 1997, Margalida et al 2008, Birdlife International 2012. Within southern Africa, where the breeding population has declined in both numbers (32-51%) and range (27%) over the past 5 decades (Krüger et al 2014), the species was recently up-listed to Critically Endangered (Krüger in press).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there would be fewer incidences of other negative factors threatening the populations of carrion eaters depending on intensive livestock such as the ingestion of veterinary drugs and pathogen transmission (Blanco et al 2007;Lemus et al 2008). Also, a higher availability of carcasses would reduce the probability of ingestion of poisoned preys (Margalida et al 2008). It is necessary for EU legislation and the regulation of the states and regions to have enough flexibility to authorize owners of extensive operations to abandon the carcasses of their livestock in order to sustain populations of avian scavengers (Donázar et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…So far, most of the studies on the causes of mortality of wild raptors have focused on single species (Real et al 2001;González et al 2007;Margalida et al 2008) or have assessed the impact of single threats, such as power lines (Lehman et al 2007) or wind farms (Drewitt & Langston 2006;Bernardino et al 2013). Assessing mortality causes is generally hard to pursue due to the difficulty in finding dead or dying wildlife and tracking animals until their death.…”
Section: Introductionmentioning
confidence: 99%